2021
DOI: 10.3389/fmed.2021.634882
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Attenuates Experimental Contrast-Induced Nephrology: A Role for the Janus Kinase 2/Signal Transducer and Activator of Transcription 3 Signaling Pathway

Abstract: The aim of the present study was to investigate the effect of erythropoietin (EPO) on contrast-induced nephrology (CIN) in vivo and in vitro. Male C57BL/6J mice were divided into four groups: control, CIN (iohexol 6.0 g/kg), EPO (3,000 IU/kg), and CIN+EPO. Hematoxylin and eosin (H&E) staining and biochemical index analyses were performed to evaluate renal injury. The cellular proliferation rate was detected using the Cell Counting Kit-8 (CCK-8) assay. In addition, a terminal deoxynucleotidyl transferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…CTSV, a lysosomal cysteine protease, is expressed at increased levels in HCC and is an independent prognostic risk factor for HCC survival, and elevated CTSV expression is strongly correlated with an adverse prognosis in HCC ( Jing et al, 2018 ). EPO is a pleiotropic cytokine that regulates multiple cellular activities and attenuates pyroptosis ( Yang et al, 2021 ). EPO is increased in HCC and its production is inversely correlated with the overall prognosis of HCC ( Ke et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…CTSV, a lysosomal cysteine protease, is expressed at increased levels in HCC and is an independent prognostic risk factor for HCC survival, and elevated CTSV expression is strongly correlated with an adverse prognosis in HCC ( Jing et al, 2018 ). EPO is a pleiotropic cytokine that regulates multiple cellular activities and attenuates pyroptosis ( Yang et al, 2021 ). EPO is increased in HCC and its production is inversely correlated with the overall prognosis of HCC ( Ke et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the activation of NF-κB and STAT3 takes place in dissimilar cytokines; while TNF potently activates the former, IL-6 strongly activates STAT3. A previous study also demonstrated the potential ability of erythropoietin to activate NF-κB by activating JAK2 kinase [ 48 ]. Therefore, the inhibition of JAK2 kinase activation could be pivotal to suppressing STAT3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Both families have been confirmed in mammals. Animals AKI or ischemia–reperfusion (I/R) damage models have demonstrated the involvement of JAK 1 and 2 as well as STAT 3, 5, and 6 in the development of AKI 13 . It is generally recognized that many cytokines, including TNF-α and IL-6, have a role in the immune response via the JAK/STAT pathway 14 .…”
Section: Introductionmentioning
confidence: 99%